Стратегічні вектори розвитку транспортних підприємств в умовах глобалізації - Ладиженський, Е.Д.; Соколов, А.В.; Мірошниченко, І.С. (Економічний вісник Донбасу, 2023)
Стаття присвячена актуальним питанням розвитку транспортних підприємств в сучасних умовах. Актуальність до-
слідженої проблематики викликана посиленою увагою до розвитку транспортної галузі, як пріоритетної у економіці країни. Метою дослідження є обґрунтування стратегічних напрямів розвитку транспортних підприємств з урахуванням сучасних стратегічних орієнтирів транспортної галузі. У статті розглянуті основні тенденції функціонування транспортних підприємств в Україні. Досліджено питання стратегічних орієнтирів у розвитку підприємств транспортної галузі. Вивчено основні положення Національної транспортної стратегії України та її вплив на формування стратегічних орієнтирів безпосередньо на транспортних підприємствах. Виявлено взаємозв’язок стратегічних напрямів розвитку транспортних підприємств та оперативних цілей і завдань забезпечення їх діяльності. The article is devoted to topical issues of the development of transport enterprises in modern conditions. The topicality of the study is due to the increased attention paid to the development of the transport sector, which is a priority in the country’s economy. Efficient operation of transport enterprises is considered essential to ensure a high level of competitiveness of the country as a whole. Transport enterprises are a decisive instrument for achieving the social and financial objectives of the country’s sector and economy. The purpose of the study is to justify strategic directions for the development of transport enterprises, taking into account modern strategic orientations of the transport industry. The article discusses the main trends in the operation of transport enterprises in Ukraine. The question of strategic guidelines for the development of transport enterprises was investigated. The main provisions of the National Transport Strategy of Ukraine were studied, as well as its impact on the formation of strategic guidelines directly in transport enterprises. The achievement of strategic orientations is conditioned by adequate operational planning, which ensures the ongoing and strategic activities of enterprises at the same time. The relationship between the strategic directions of the development of transport enterprises and the operational goals and tasks for their operation has been identified. The strategic orientation of an individual enterprise should take into account the positive results achieved in the entire industry. The priorities that will improve the competitiveness of domestic transport enterprises are: unhindered mobility and interregional integration; safe, clean and energy-efficient transport; innovative development of the transport industry and global investment projects; competitive and efficient transport system. The introduction of strategic guidelines will: make it possible to establish a single transport space; strengthen regional and international integration of enterprises in the national transport system; increase the efficiency and quality of transport services; increase exports and transit through the country; increase the profitability of transport enterprises.